Improving water productivity: how do we get more crop from every drop - International Water Management Institute; Comprehensive Assessment of Water Management in Agriculture (International Water Management Institute, 2003)
Based on research presented in the book ?Water Productivity in Agriculture : Limits and Opportunities for Improvement? by J.W. Kijne, R. Barker and D. Molden. If current trends continue, the water crisis?which is already beginning to rear its head in many countries through depleted groundwater aquifers, dried-up rivers and wetlands, and frequent water shortages?will indeed become a global problem. A recent study by the International Food Policy Research Institute (IFPRI) and the International Water Management Institute (IWMI) projects that if present trends continue, by 2025 competition from growing cities and industry worldwide will limit the amount of water available for irrigation, causing annual global losses of 350 million metric tons of food production - slightly more than the entire current U.S. grain crop. The environment will also sustain further damage, as water from this already thirsty sector is diverted to agriculture, households and industry. If levels of investment in sustainable water policy and management decrease over the next 20 years, the result will be major declines in food production and skyrocketing food prices. research done over the past decade shows that by improving the productivity of water on irrigated and rain-fed lands, we can have enough water for cities, industry and nature. But this requires a commitment to institutional and management reforms, and substantial investment in crop research, technology, and infrastructure.